(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1915)
The Dalmeny sarcophagus has animal carvings in bold relief at both ends. On the side there is a line of figures standing under an arcading of Norman style, whose arches and supporting columns were more or less clearly indicated at different points in the worn sculpture. This is believed to be a representation of Christ and the twelve Apostles, six placed on each side of the central figure of our Lord. The lid of the sarcophagus does not survive. The churchyard also contains a number of elaborate table-stones, a large representation of the symbolic designs common to the Lothians, and a few headstones. In the old churchyard of Edzell parish are a number of finely ornamented tombstones, dating from the eighteenth century, several architectural features of the pre-Reformation church and a sculptured slab. At Lethnot there are two very elaborate table-stones and eight erect stones, all dating from or near to 1750. There are three massive inscribed stones at Stracathro.